Discovery of the genus Rybocyclops Dussart, 1982 (Crustacea, Copepoda, Cyclopoida) in subterranean groundwaters of southeastern India, with the description of a new species and its biogeographic significance - Reddy, Yenumula Ranga; Defaye, Danielle (Zootaxa, 2008)
Rybocyclops Dussart, 1982 is a little-known stygobitic genus, hitherto represented by its type and only species, R. pauliani (Lindberg, 1954), from Madagascar. A second species, named Rybocyclops dussarti sp. nov., is described herein from an agricultural bore-well in southeastern India. The new species has a unique combination of morphological characters, which, inter alia, include: genital double-somite enlarged; anal operculum moderately large; furcal rami somewhat outcurved and about twice as long as wide; female antennules 11-segmented; legs 1–4 with spine formula 2.2.2.2, and setal formula 5.5.5.4; legs 1 and 4 without seta on inner margin of coxa and basis; leg 4 male with one seta more than in female on second endopodal segment; leg 5 fused to somite and represented by vague protuberance, bearing three setae; and leg 6 reduced to two setae. The generic diagnosis is partially amended for accommodating the new species. The discovery of R. dussarti sp. nov. is of much biogeographic interest because it is the first record of Rybocyclops from Asia and only the second freshwater stygobitic cyclopoid taxon from India, with apparent Gondwanan distribution.